Selective extinction of Triassic marine reptiles during long-term sea-level changes illuminated by seawater strontium isotopes - Kelley, Neil P.; Motani, Ryosuke; Jiang, Da-yong; Rieppel, Olivier; Schmitz, Lars (Palaeogeography, palaeoclimatology, palaeoecology, 2014)
The relationship between cycles of sea-level change and marine diversity has long been the subject of debate. Large predators may be particularly sensitive to changes in habitat availability and marine productivity driven by changes in sea-level, especially those dependent on nearshore benthic food resources. To test this relationship, we compared the proportional diversity of differing marine reptile ecotypes through the Triassic with the isotopic composition of seawater strontium (87Sr/86Sr), a geochemical index linked to tectonically controlled sea-level change. The proportional abundance of marine reptiles adapted toward a diet of shelled prey rose during times of rapid sea-level rise and fell during times of rapid sea-level fall, while open water forms were more resistant to these changes. Our results indicate that the rate of sea-level change, rather than the absolute magnitude of sea-level or flooded shelf area, played a role in shaping patterns of ecological diversification and ecologically selective extinction during the Triassic. The link between the isotopic composition of seawater strontium and the evolution of marine reptiles demonstrates that sea-level change played an important role in the structuring of marine ecosystems over geologic time. ► We compare marine reptile diversity to seawater strontium values in the Triassic. ► During intervals of rising sea-level, durophagous species were relatively abundant. ► During intervals of falling sea-level, these species went extinct. ► Sea-level changes caused ecologically selective extinction among marine reptiles.